Pollutant Emissions from Brick Kilns and Their Effects on Climate Change and Agriculture - Muhammad Asif; Sobia Saleem; Anum Tariq; Muhammad Usman; Rida Ahtizaz Ul Haq (Universitas Pendidikan Indonesia (UPI), 2021)
Continuous increase in population has resulted in increased demand for building material. Bricks are the major building material and are a fast-growing industrial sector in many countries such as Pakistan, China, India, and Bangladesh. Despite its integral role, it is among the top three factors that cause the emission of harmful pollutants that not only affect our climate and human health but also effecting agriculture sectors to a great extent. Brick kilns emit gases like SO2, CO, Black Carbon, CO2, NOx, PM, etc., that affect our biotic and abiotic components of the ecosystem. So, the objective of this paper is twofold. Firstly, it has been focused on the pollutants emissions from brick kilns, their effects on climate and agriculture sectors. Secondly, the possible techniques have been discussed that can be used to reduce or eliminate its harmful impacts. It was found that the pollutant emissions from brick kilns like SOx, NOx, CO2, CO, unburnt hydrocarbons, Particulate matter, heavy metal, and various other compounds have a significant effect on the surrounding environment, climate and agriculture field in the vicinity of brick kilns. If the proper technology for reducing pollutants will not be installed in the brick kiln, there might be a serious disadvantage of climate and especially in the agriculture field in the vicinity of brick kilns.